Assistance in Learning Activities Using Games and Songs Media to Increase Learning Motivation and English Vocabulary of Class 3 Students of SDN 3 Bebalang in 2023 - Yanti, Ni Kadek Napa; Numertayasa, I Wayan; Pradnyana, Putu Beny (CV. Media Inti Teknologi, 2024)
English has become a globally dominant language that is widely used in various sectors of life. Its significance in international communication and its widespread use in various fields can emphasize the importance of acquiring English language skills for personal and professional growth. This study aims to investigate efforts to improve motivation in learning English through songs and games on the topics of days of the week and parts of the body. This research adopts the Peer Assisted Learning Strategies (PALS) methodology, which involves (1) identifying the teacher's problems, (2) conducting a needs analysis to address the identified issues, (3) designing coaching and mentoring programs, (4) implementation, (5) monitoring and observing the activities, and (6) reporting and follow-up. The subjects of this study are 15 third-grade students from SDN 3 Bebalang. The focus of this research is on motivation and English vocabulary. The results of this study indicate an improvement in English vocabulary and student motivation, students are more actively engaged in the learning process and show enthusiasm for learning English. With the positive impact shown by this research, it can be concluded that the implementation of the mentoring method using English games and songs has succeeded in achieving the stated goals, namely increasing students' learning motivation and mastery of their English vocabulary.